2007
DOI: 10.1007/s00586-007-0305-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous healing of retroperitoneal chylous leakage following anterior lumbar spinal surgery: a case report and literature review

Abstract: Cisterna chyli is prone to injury in any retroperitoneal surgery. However, retroperitoneal chylous leakage is a rare complication after anterior spinal surgery. To the best of our knowledge, only ten cases have been reported in the English literature. We present a case of a 49-year-old man who had lumbar metastasis and associated radiculopathy. He had transient retroperitoneal chylous leakage after anterior tumor decompression, interbody bony fusion, and instrumental fixation from L2 to L4. The leakage stopped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…50% to 90% of lymph fluid in cisterna chyli and thoracic duct comes from intestines and liver. Fasting before operation may decrease lymphatic flow less than 1 ml/min dramatically, while it may increase to more than 200 ml/min after a normal diet recovers [ 11 , 12 ]. The amount of the lymphatic flow may increase and the size of lymphatic ducts may be magnified under the following circumstances of hypertension and cardiac diseases, particularly mitral valve dysfunction and left ventricular aneurysm [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50% to 90% of lymph fluid in cisterna chyli and thoracic duct comes from intestines and liver. Fasting before operation may decrease lymphatic flow less than 1 ml/min dramatically, while it may increase to more than 200 ml/min after a normal diet recovers [ 11 , 12 ]. The amount of the lymphatic flow may increase and the size of lymphatic ducts may be magnified under the following circumstances of hypertension and cardiac diseases, particularly mitral valve dysfunction and left ventricular aneurysm [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anterior spinal surgery with or without diaphragm splitting is another relevant surgery to chyloretroperitoneum. The surgery below L1 level without diaphragm splitting is prone to injure the cisterna chyli or their tributaries [ 12 ]. Chylothorax may occur secondary to postoperative chyloretroperitoneum [ 12 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may have been because the NBCA mass was not sufficient to obstruct the LPA, as observed in the present case (green arrowheads in Figure 1D). In cases of LPA embolization failure, cases 12,16,17, and the present case needed ULN or ULV.…”
Section: Discussionmentioning
confidence: 56%
“…14,15 Other studies indicated that earlier radiologic interventions are preferable, particularly in severe cases with lymphatic leakage of greater than 1000 to 1500 mL/day. 16,17 Further case reports and/or clinical studies are needed in order to establish an appropriate treatment strategy; however, we are currently performing earlier radiologic interventions in an attempt to reduce hospital stays, discomfort owing to complications including hypoalbuminemia, and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Chyle production is slowed by several dietary interventions implemented as soon as the diagnosis is suspected. Some authors advocate a diet consisting of medium-chain triglycerides, which will be absorbed by the portal system, reducing the net flow through the duct (8,12,13). A more decisive approach is to cease all enteral intake while providing central hyperalimentation.…”
Section: In Addition Quantitative Criteria Have Not Been Establishedmentioning
confidence: 99%